Determinant Analysis of the Incidence of Type 2 Diabetes Mellitus in Early Adulthood at the South City Health Center - Yuriskawati Paris; Laksmyn Kadir; Yasir Mokodompis (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Type 2 Diabetes Mellitus is a non-communicable disease whose prevalence continues to increase globally, nationally, and locally. Globally, the International Diabetes Federation reports that the prevalence of diabetes reaches 10.5% in the age group of 20-79 years and is projected to increase to 783.2 million cases by 2045. In Indonesia, the number of people with diabetes reaches around 19.47 million people with a prevalence of 10.6%, placing Indonesia in fifth place in the world. Meanwhile, in Gorontalo Province in 2024, there will be 10,735 cases (4%) of Diabetes Mellitus. This condition shows an increase in the burden of disease, including in the early adulthood age group. This study aims to analyze the determinants of the incidence of type 2 Diabetes Mellitus in early adulthood at the South City Health Center. This study uses an analytical quantitative design with a cross sectional approach. The sample amounted to 87 respondents who were selected through accidental sampling techniques. Data were collected using questionnaires and direct measurements, then analyzed by Chi-Square test at a 95% confidence level (?=0.05). The results showed that 35.6% of respondents experienced type 2 Diabetes Mellitus. There was a significant association between hereditary history (p=0.000) and central obesity (p=0.033) with the incidence of type 2 diabetes mellitus. In contrast, physical activity showed no significant association (p=0.614). It is recommended to health centers to increase early screening of at-risk individuals and strengthen obesity control programs through education and lifestyle interventions.